Cost utility analysis of long acting muscarinic antagonists (LAMAs) as an alternative to long acting beta agonists (labas) for treatment of severe COPD in the South African public sector - Thompson, Peggy (My University, 2024)
Objective- The study purposed to estimate the cost-effectiveness of Tiotropium, compared with Salmeterol and Indacaterol for chronic obstructive pulmonary disease (COPD) patients within the South African public sector. Methods- A global Markov model was adapted for the local setting and developed in Microsoft Excel. Transition probabilities and data on costs, resource use and effectiveness were obtained from literature. Outcomes were calculated for 3-years in the base case, then extrapolated over a 10-year and lifetime time horizon. A 5% discounting rate was applied according to local guidelines. Cost-effectiveness was estimated as the incremental cost per quality adjusted life year (QALY). One-way and probabilistic sensitivity analyses were conducted to consider model uncertainty. Results- When compared with Indacaterol (300µg), Tiotropium was dominant (less costly and more effective) across all time horizons. Conversely, Tiotropium was not cost-effective when compared with Indacaterol (150µg) and dominated by Salmeterol over the 3- and 10-year time horizons. The resulting ICURs exceeded the estimated willingness to pay thresholds for all scenarios. The deterministic sensitivity analysis revealed the new intervention cost and utility for mild COPD impacted most on intervention cost effectiveness. Conclusion- Tiotropium was deemed not cost-effective at the proposed price, when compared to usual care for COPD. A price reduction should be considered, to determine the feasibility of displacing existing maintenance therapies. Indacaterol 150µg appeared more cost-effective at the current price and effectiveness demonstrated.
A research report submitted in partial fulfilment of the requirement for the degree of Masters of Public Health to the Faculty of Health Sciences, University of the Witwatersrand, School of Public Health, Johannesburg, 2023
Keywords: Tiotropium; SDG-3: Good health and well-being; SDG-17: Partnerships for the goals